Micro/nanometric processing of CVD diamond with femtosecond laser pulses - Nolasco, Lucas Konaka (2025)
Diamond is one of the most known allotropic forms of carbon, famous for its extreme properties such as high hardness and thermal conductivity. It possesses a wide transparency window (from ultraviolet up to the microwave region), high refractive index and other interesting features. In addition, as a wide band gap semiconductor, it presents an energy gap of 5.47 eV, and even displays interesting nonlinear optical properties such as two and three-photon absorption, and thus, such material is highly sought-after for opto-photonics technologies. Furthermore, such material hosts many defects associated with trapped electrons or holes. The Nitrogen-Vacancy color center, in particular, is its most notorious defect, with possible applications in Quantum Photonics as a quantum emitter of light or even optically accessed qubits. That said, amidst the many diamond processing techniques, femtosecond laser micromachining distinguishes itself due to its capacity to fabricate micro/nanometric devices with high precision in either the surface or bulk, capitalizing on the nonlinear optical effects. Therefore, in this work, the ablation threshold fluence (minimal energy density required for material removal) was extensively explored over a wide range of fs-laser pulses per spot through the zero-damage method to verify the incubation effect, which was evaluated via an exponential defect accumulation model. From such analysis, it was determined that, at 515 nm, the decrease in the threshold fluence value was more efficient when compared to 1030 and 343 nm cases, and it was hypothesized that NV color centers present within the micromachined region aided the light absorption mechanisms, since such defect is known to absorb at 532 nm. The defects presence was confirmed via Raman spectroscopy and photoluminescence analyses, which prompted a subsequential study regarding the optimal experimental parameters for NV color center generation via ultrashort laser pulses. It was determined that the color center generation is proportional to the peak laser fluence used during micromachining, while it is inversely proportional to the pulse duration and excitation wavelength. In addition, a vacancy generation via fs-laser micromachining first principles model was proposed, where the two, three and five-photon absorption cross-sections of diamond were determined. Moreover, Optically Detected Magnetic Resonance (ODMR) measurements were performed on the fabricated defects, confirming their presence as well as determining their coherence time (longitudinal relaxation time) of 3.2 ms. Finally, machine learning techniques (principle component analysis/artificial neural network) were employed as an alternative procedure for analyzing the NV color center generation data, which reached the same conclusions regarding the optimal experimental conditions, thus revealing it to be promising tools for future microfabrication experiments. Hence, this work is an important step toward mastering diamond processing and color center generation via ultrashort pulses.